335 DIFFERENTIALLY EXPRESSED MICRORNAS AND PREDICTIVE TARGET GENES IN BASALOID SQUAMOUS CELL CARCINOMA OF THE ESOPHAGUS. (17th September 2021) - Nakamura, Jiro; Furuya, Shinji; Hagio, Kotaro; Maruyama, Suguru; Shiraishi, Kensuke; Shimizu, Hiroki; Akaike, Hidenori; Hosomura, Naohiro; Kawaguchi, Yoshihiko; Amemiya, Hidetake; Kawaida, Hiromichi; Sudo, Makoto; et al.
Abstract:  : Background/Aim: Esophageal cancer is the sixth leading cause of cancer-related deaths worldwide. Esophageal squamous cell carcinoma (ESCC) is considered as one of the most aggressive carcinomas of the gastrointestinal tract. Basaloid squamous cell carcinoma of the esophagus (BSCCE) is reported to have a poorer prognosis compared to conventional ESCC. The current study aimed to elucidate molecular differences between BSCCE and ESCC, using miRNA profiling and predictive target gene searching. Methods: Materials and Methods: Four BSCCE and 94 ESCC patients who underwent esophagectomy were selected for this study. Cell lines were used for target gene validation. Total RNA samples, extracted from formalin-fixed paraffin-embedded blocks, were used for microarray profiling and validation of the miRNAs, selecting the candidate target genes, and elucidating their clinicopathological features. Furthermore, total RNA samples, extracted from miRNA mimic- and inhibitor-transfected cells in cell line experiments, were used for target gene validation. Both miRNA and mRNA quantifications were performed by quantitative reverse transcription-polymerase chain reaction. Results: The microarray analysis revealed seven highly expressed miRNAs (miR-205-5p, −4732-5p, −1246, −3687, −3175, −6087, and − 1587) in the BSCCE patients when compared with control. We selected miR-4732-5p and − 3687 for the validation study, and target gene investigations were conducted for miR-3687 ultimately. Several candidates were selected after searching for the target genes via TargetScan and in the literature. Through a pilot and a validation study, progesterone receptor membrane component 2 (PGRMC2) was identified as a target gene. Further investigations revealed that PGRMC2 was associated with tumor size clinicopathologically. Conclusion: miR-3687 may constitute a candidate marker of aggressiveness in BSCCE, and PGRMC2 is one of its target genes. Moreover, the gene may play a role in cell proliferation and local progression. Although the current study included only a small number of samples, this is the first report regarding differentially expressed miRNAs and predictive target genes in BSCCE patients.